Analisis Kejadian Anemia Pada Remaja Putri Sekolah Menengah Atas di Wilayah Kerja Puskesmas Pembina Kota Palembang Tahun 2024 - Damai Yanti, Ria; Asiani, Gema; Harokan, Ali (Avicenna: Jurnal Ilmiah, 2024)
Background: Anemia is a body condition where the hemoglobin (Hb) level in the blood is lower than normal. Adolescent girls are one of the groups that are prone to suffering from anemia, because at that time they are menstruating and have less knowledge about anemia. The problem of anemia in adolescent girls is in the moderate category (20-39%) in the 2019 WHO standards. Adolescent girls who suffer from anemia when they become pregnant mothers are at risk of giving birth to low birth weight babies (LBW) and stunting. Adolescent girls during puberty are at high risk of experiencing iron deficiency anemia. This study aims to determine the analysis of the incidence of anemia in high school teenage girls in the work area of ​​the Pembina City Health Center in Palembang in 2024. Method: This research is a quantitative study with a cross sectional approach. This research was conducted on March 25 - May 15 2024. The population of this research was teenage girls in class 10 of high school in the work area of ​​the Pembina City Health Center, Palembang, totaling 87 samples, using a stratified proportional random sampling technique. Primary data was obtained through interviews using a questionnaire and anemia data for high school teenage girls was obtained from the hemoglobin examination report at the Pembina Public Health Center, Palembang City. Results: Statistical test using chi square with logistic regression with a significance level (α=0.05). The results of the study showed that there was a relationship between level of knowledge (p=0.000), parents’ income (p=0.014), nutritional status (p=0.008), compliance with blood supplement tablet consumption (p=0.001), and the role of government (Puskesmas) and teacher support. UKS (p=0.006) with the incidence of anemia in high school teenage girls in the working area of ​​the Pembina City Health Center in Palembang in 2024. However, there was no relationship found between the length of menstruation and the incidence of anemia in high school teenage girls in the working area of ​​the Pembina City Palembang Health Center in 2024. 2024 (p=0.785). Multivariate analysis showed that the dominant variable associated with the incidence of anemia in high school adolescent girls was the level of knowledge (p=0.000; OR 12.018). Conclision: Based on the results of the research, the researcher hopes that the Palembang City Pembina Community Health Center will continue to actively provide health education to young women, especially education about anemia and carry out anemia screening and provide feedback on the results of the examination to the school so that it can be followed up by UKS teachers and Nutritional interventions were carried out on adolescent girls with anemia and malnutrition by Pembina Community Health Center nutrition officers. One day is set as a day for consuming blood supplement tablets at school so that it can increase compliance in consuming blood supplement tablets among young women at school. Keywords: Anemia, Teenagers, Women